Behavioural and Neurophysiologic Features of State Dissociation: A Brief Review of the Literature and Three Descriptive Case Studies - Alberto Raggi; Filomena I.I. Cosentino; Bartolo Lanuzza; Raffaele Ferri (Behavioural Neurology)
Wakefulness, rapid eye movement (REM) and non-REM sleep are not always mutually exclusive conditions, as commonly assumed. In some cases, the declaration of any state may be incomplete and states can fluctuate rapidly, resulting in peculiar behavioural syndromes such as narcolepsy, REM sleep behaviour disorder and status dissociatus. We briefly introduce this topic and discuss three suggestive clinical cases.